LATE CRETACEOUS TETRAPODS DIVERSITY OF THE TRIÂNGULO MINEIRO REGION (MINAS GERAIS STATE, BRAZIL) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2014)
The Turonian-late Maastrichtian Adamantina, Uberaba and Marília Formations crop out at the Triângulo Mineiro region, Minas Gerais State, Brazil, yielding a rich continental biota. Invertebrate and vertebrate taxa from underlying and overlying strata, as well as biostratigraphical correlations with other fossil sites in Argentina, suggest an Upper Cretaceous age for this biota. The diversity of the biota recorded from the Adamantina, Uberaba and Marília Formations of Triângulo Mineiro region is summarized here and includes; frogs, lizards, turtles, crocodiliforms, titanosaurs, abelisaurids and carcharodontosaurids dinosaurs and aves. This tetrapod content provides important clues to help understand fauna from elsewhere, such as those from the Cretaceous of Gondwana.
Keywords: Upper Cretaceous; Triângulo Mineiro; Adamantina; Uberaba and Marília Formations; tetrapods